A Macrocyclic 2, 2′‐Bibenzimidazole Ruthenium(II) Chromophore as a Versatile Building Block for Supramolecular Devices. Issue 26 (11th August 2014) - Sorsche, Dieter; Rau, Sven
Abstract: We present the synthesis of a macrocyclic ruthenium(II) complex that combines the versatile photophysics and supramolecular chemistry of biimidazole ruthenium(II) chromophores with a macrocyclic geometry that allows for its introduction into mechanically interlocked frameworks. Structural information on the core framework was gained from a solid‐state structure. The new supramolecular building block shows that the principal photophysics of the ruthenium chromophore, that is, the cation‐driven light‐switch effect, are retained during the formation of the macrocycle. Abstract : A new pH‐ and cation‐switchable ruthenium(II) chromophore is presented. Owing to the versatility of the macrocyclic 2, 2′‐bibenzimidazole ligand, the complex presents itself as an attractive new building block for supramolecular arrays.